Sosialisasi BNN terhadap Perilaku Masyarakat dalam Menghadapi Penyalahgunaan Narkoba - Maharani, Dhiastri Heru; Suyuti, Muh Hikamudin (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
Drug abuse is a serious problem that has a negative impact on public health and social stability. The National Drug Dispatch (BNN) plays an important role in implementing socialization to raise public awareness about the risks of substance abuse. This study aims to analyze the effectiveness of BNN's socialization program to influence public behavior towards substance abuse. The method used is a survey with a quantitative approach involving respondents from different levels of society. The consequence is that the socialization that has been made significantly by BNN to increase public knowledge and awareness of drugs, as well as to increase public knowledge and awareness of drugs, to change abuse more consciously. The findings are expected to provide BNN recommendations on the design of more effective and sustainable socialization programs and increase community participation in efforts to prevent substance abuse.